Delignification of palm fiber by microwave assisted chemical pretreatment for improving energy efficiency - Laghari, S.M. (Malaysian Abstracting and Indexing System, 2016)
Fossils fuels are main source of energy. However, their depletion has caused widespread concern. In recent years, utilization of agricultural wastes for energy has received a lot of attention. Lignocellulosic biomass is an abundantly available agricultural waste. It is a candidate for economic and environmental friendly source of biofuel production. However, high lignin content of the biomass reduces its digestibility and energy recovery. Suitable pretreatment of biomass can degrade the lignin content and enhance its conversion to biofuel. This work studied the effects of various microwave assisted chemical pretreatments on delignification of palm fiber to improve energy recovery. A total of 12 solutions using four chemicals, namely, sulphuric acid, sodium hydroxide, hydrogen peroxide, and sodium carbonate with 3 different concentrations i.e. 2, 3.5, and 5 were prepared. 1 g of palm fiber was pretreated in 10 ml of each solution, for 48 h. The solution along with the biomass was then heated by microwave irradiation for 5 min. The results showed that the pretreatments performed were effective in reducing lignin content and increasing cellulose content of the samples. Sodium hydroxide and hydrogen peroxide were most suitable for delignification of palm fiber. Treatment with these chemicals reduced the lignin content and changed the C/N ratio to the optimum range. This increased cellulose content enhances energy potential to produce biofuel by conversion to ethanol or biogas.